An unprecedented binuclear cadmium dithiocarbamate adduct: bis[μ2-N-(2-hydroxyethyl)-N-isopropylcarbamodithioato-κ3S:S,S′]bis{[N-(2-hydroxyethyl)-N-isopropylcarbamodithioato-κ2S,S′](3-{(1E)-[(E)-2-(pyridin-3-ylmethylidene)hydrazin-1-ylidene]methyl}pyridine-κN)cadmium]} dihydrate - Arman, Hadi D.; Poplaukhin, Pavel; Tiekink, Edward R. T. * (International Union of Crystallography, 2016)
The asymmetric unit in the title binuclear compound, [Cd(C6H12NOS2)2(C12H10N4)]2·2H2O, comprises a CdII atom, two dithiocarbamate (dtc) anions, a monodentate 3-pyridinealdazine ligand and a lattice water molecule. The binuclear molecule is constructed by the application of inversion symmetry. One dtc ligand simultaneously chelates one cadmium atom and bridges the centrosymmetric mate, while the other dtc ligand is chelating only. This leads to a centrosymmetric [Cd(dtc)2]2 core to which are appended two 3-pyridinealdazine ligands. The resulting NS5 donor set is based on an octahedron. The three-dimensional molecular packing is sustained by hydroxyl-O-H(hydroxyl) and water-O-H...O(hydroxyl) hydrogen bonding, leading to supramolecular layers parallel to (101) which are connected by water-O-H...N(pyridyl) hydrogen bonding; additional C-H...O, S [pi](chelate ring) interactions are also evident. The retention of the central [Cd(dtc)2]2 core upon adduct formation is unprecedented in the structural chemistry of the zinc-triad dithiocarbamates.